Licensing Under Bertrand Competition Revisited. (27th May 2015) - Colombo, Stefano
Abstract : This note indicates that the derivation of the royalty contract for licensing in Wang and Yang ( A ustralian   E conomic   P apers, 39 (1999) 106–119) is not correct. As a consequence, the profits of the innovator in the case of royalty licensing are underestimated.